2014
DOI: 10.1111/ipd.12135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic dental injuries and its association with binge drinking among 12‐year‐olds: a population‐based study

Abstract: A higher prevalence rate of traumatic dental injuries was found among 12-year-olds who engaged in binge drinking. The high rate of alcohol intake among adolescents is worrisome considering the vulnerability of this population due to the intense transformations that occur in the transition from childhood to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 27 publications
1
26
0
6
Order By: Relevance
“…Three socioeconomic variables were analyzed in the present investigation (monthly household income, type of school, and mother's schooling), but none demonstrated a statistically significant association with TDI, which is in agreement with data described in previous studies . A significant number of investigations which used the same socioeconomic factors as those used in this study, many of which were performed in Brazil, also did not find association with TDI . A study, conducted in the same city of the present study, but with a higher age group, also showed no association between socioeconomic factors and TDI .…”
Section: Discussionsupporting
confidence: 90%
“…Three socioeconomic variables were analyzed in the present investigation (monthly household income, type of school, and mother's schooling), but none demonstrated a statistically significant association with TDI, which is in agreement with data described in previous studies . A significant number of investigations which used the same socioeconomic factors as those used in this study, many of which were performed in Brazil, also did not find association with TDI . A study, conducted in the same city of the present study, but with a higher age group, also showed no association between socioeconomic factors and TDI .…”
Section: Discussionsupporting
confidence: 90%
“…As for epidemiologic studies, among the 631 titles and abstracts screened, 229 full texts were potentially eligible and 77 of them were excluded for various reasons, thus leaving 152 primary studies (Figure ). Of these, 102 studies were considered for TDI prevalence to permanent teeth (Unpublished Material 2), 46 for TDI prevalence to primary teeth (Unpublished Material 3), 42 for TDI prevalence among 12‐year‐old children…”
Section: Resultsmentioning
confidence: 99%
“…Many risk factors are related to TDI, which has a complex causal network that encompasses individual characteristics as well as environmental (both physical and social) aspects. Accentuated overjet is among the most widely studied predisposing factors and has a confirmed associated with TDI, which was corroborated by the results of the present investigation. A taller height is another risk factor reported for the occurrence of TDI .…”
Section: Discussionmentioning
confidence: 97%